2022
DOI: 10.3389/fpls.2022.993244
|View full text |Cite
|
Sign up to set email alerts
|

Detection method of wheat spike improved YOLOv5s based on the attention mechanism

Abstract: In wheat breeding, spike number is a key indicator for evaluating wheat yield, and the timely and accurate acquisition of wheat spike number is of great practical significance for yield prediction. In actual production; the method of using an artificial field survey to count wheat spikes is time-consuming and labor-intensive. Therefore, this paper proposes a method based on YOLOv5s with an improved attention mechanism, which can accurately detect the number of small-scale wheat spikes and better solve the prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Our attention was focused on the Yolo algorithm because it has an impressive balance of accuracy and speed in the field of object detection. In our research, we found that Yang et al [28] and Gong et al [29] used an improved Yolov4 algorithm, while Zang et al [30] used an improved Yolov5 algorithm. These improvements mainly included using attention mechanisms to improve detection accuracy and using lightweight models to improve algorithm real-time performance and deployability.…”
Section: Introductionmentioning
confidence: 61%
“…Our attention was focused on the Yolo algorithm because it has an impressive balance of accuracy and speed in the field of object detection. In our research, we found that Yang et al [28] and Gong et al [29] used an improved Yolov4 algorithm, while Zang et al [30] used an improved Yolov5 algorithm. These improvements mainly included using attention mechanisms to improve detection accuracy and using lightweight models to improve algorithm real-time performance and deployability.…”
Section: Introductionmentioning
confidence: 61%
“…The term “convolutional neural network” refers to the network’s use of a mathematical operation known as convolution. The CNN is then trained to examine the object’s features in order to predict it [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, the two-stage detection network used in the count-by-detection method ignores the real-time requirements of field applications. Notably, the YOLO series, another commonly used object detection method, is faster and more efficient than other methods and can meet the practical needs of plant detection and counting problems (Yang B, et al, 2021;Lyu et al, 2022;Zang et al, 2023). However, the accuracy of tassel detection still needs to be improved (Zou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%